Effectiveness of Quantum Physics Learning Tools Using Blended Learning Models to Improve Critical Thinking and Generic Science Skills of Students - Aris Doyan; Susilawati Susilawati; Saprizal Hadisaputra; Lalu Muliyadi (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to determine the effectiveness of quantum physics learning tools using blended learning models to improve the critical thinking and generic science skills of students. The learning device was developed using a 4-D model which includes the stages of definition, design, development, and dissemination. Learning devices that have been declared valid then conducted a limited-scale trial in the Physics education undergraduate program at the University of Mataram, which consisted of thirty students. Analysis of increasing critical thinking and science generic skills using the n-gain (g) test. The results of the n-gain analysis for all aspects indicate that the student's critical thinking and generic science skills are in the medium and high categories. These results indicate that the use of quantum physics learning using a blended learning model is effective in improving students' critical thinking and generic science skills